Evolutionary Insights from a Genetically Divergent Hantavirus Harbored by the European Common Mole (Talpa europaea) - Kang, Hae Ji (Public Library of Science, 2009)
BACKGROUND: The discovery of genetically distinct hantaviruses in shrews (Order Soricomorpha, Family Soricidae) from widely separated geographic regions challenges the hypothesis that rodents (Order Rodentia, Family Muridae and Cricetidae) are the primordial reservoir hosts of hantaviruses and also predicts that other soricomorphs harbor hantaviruses. Recently, novel hantavirus genomes have been detected in moles of the Family Talpidae, including the Japanese shrew mole (Urotrichus talpoides) and American shrew mole (Neurotrichus gibbsii). We present new insights into the evolutionary history of hantaviruses gained from a highly divergent hantavirus, designated Nova virus (NVAV), identified in the European common mole (Talpa europaea) captured in Hungary. METHODOLOGY/PRINCIPAL FINDINGS: Pair-wise alignment and comparison of the full-length S- and L-genomic segments indicated moderately low sequence similarity of 54–65% and 46–63% at the nucleotide and amino acid levels, respectively, between NVAV and representative rodent- and soricid-borne hantaviruses. Despite the high degree of sequence divergence, the predicted secondary structure of the NVAV nucleocapsid protein exhibited the characteristic coiled-coil domains at the amino-terminal end, and the L-segment motifs, typically found in hantaviruses, were well conserved. Phylogenetic analyses, using maximum-likelihood and Bayesian methods, showed that NVAV formed a distinct clade that was evolutionarily distant from all other hantaviruses. CONCLUSIONS: Newly identified hantaviruses harbored by shrews and moles support long-standing virus-host relationships and suggest that ancestral soricomorphs, rather than rodents, may have been the early or original mammalian hosts.